Impact of Techno-corp Investment on Technology Startup Growth in Asia: Case Study of Several Portfolio Startups - Khairunnisa; Zakaria, Mahmud (Journal of Technology and Computer, 2025)
This study examines the impact of Techno-corp's investments on the growth of technology startups in Asia through a qualitative case study approach. Analyzing five to seven portfolio startups across fintech, AI, e-commerce, and SaaS sectors, the research evaluates four key growth indicators: financial performance, market expansion, technological innovation, and operational efficiency. Findings reveal that startups experienced an average revenue growth of 45% within two years post-investment, with significantly improved profit margins and operational efficiency. Beyond financial support, Techno-corp's strategic mentorship and industry networks proved instrumental in facilitating market expansion—enabling startups to enter new geographical markets and secure enterprise partnerships. The study highlights how Techno-corp-backed startups accelerated innovation cycles, exemplified by AI-driven product enhancements (e.g., a 30% improvement in customer service response times) and blockchain-based security solutions. Operational efficiencies were achieved through automation, reducing costs by up to 25%. These results demonstrate that corporate investment, when combined with strategic guidance, addresses critical scaling challenges more effectively than traditional venture capital alone. The research contributes to academic discourse on corporate venture capital while offering practical insights for investors, policymakers, and entrepreneurs seeking to optimize startup growth strategies in Asia’s competitive tech landscape. Limitations include the focus on a single corporate investor, suggesting avenues for future comparative studies.